Central Effects of 3-Iodothyronamine Reveal a Novel Role for Mitochondrial Monoamine Oxidases - Laurino, Annunziatina; Landucci, Elisa; Raimondi, Laura (Frontiers in Endocrinology, 2018)
3-iodothyronamine (T1AM) is the last iodinated thyronamine produced by thyroid hormone (TH) metabolism and supposed to mediate TH non-genomic effects. From its identification in rodent tissues (Scanlan et al., 2004), T1AM was included within the family of the trace amines (TAs) and identified as an endogenous ligand for trace amine associated receptors (TAARs), a family of constitutively active G protein-coupled receptors with species and tissue specific expression cross-talking with the dopaminergic and the serotoninergic transmission (Berry et al., 2017; Rutigliano et al., 2018). This latter feature raised the interest around TAAR agonists, and then on T1AM, as potential treatments for controlling craving, pain and neuropsychiatric illnesses. Consistently, the determination of endogenous T1AM brain levels or T1AM pharmacological administration would play diagnostic or therapeutic roles respectively in clinical manifestations of diseases involving dopamine release. However, after more than 10 years from T1AM discovery, whether central effects described following pharmacological administration of T1AM can be ascribed to TAAR activation remains an open issue and we have no indications of T1AM levels in psychiatric or in drug-abusing patients. An important contribution to this uncertainness derives from the lack of pharmacological antagonists of TAARs with favorable pharmacokinetic features for in vivo administration. Instead, based on the current knowledge, T1AM presents a puzzling pharmacological profile suggesting a role as a cell messenger, behaving as a hormone and/or a neuromodulator, a function likely mediated also by 3-iodothryoacetic acid (TA1), the product of T1AM non-microsomal phase-I metabolism. T1AM may also interact with high affinity targets including G-protein coupled receptors as TAAR1, or ion channels (Khajavi et al., 2017) (Laurino et al., 2016a) (Lucius et al., 2016). We here summarize and discuss evidence indicating that behavioral effects of T1AM deserve to receive the attention of the investigators since, in the central nervous system, the pharmacokinetic features of this amine include a novel role for mitochondrial monoamine oxidases (MAO). T1AM pharmacokinetic: few notes on tissue distribution Consisting evidence indicates that the tandem mass spectrometry represents the most reliable method to determine T1AM tissue levels, whereas some difficulties remain for measuring T1AM plasma levels (Lorenzini et al., 2017) because T1AM